Group III-Nitride Nanowires as Multifunctional Optical Biosensors - Hölzel, Sara Sibylle; Justus Liebig University Giessen (My University, 2018)
The application of InGaN/GaN nanowire heterostructures (NWHs) and GaN nanowires (NWs) as electrodes for the simultaneous photoelectrochemical and optical detection of charge transfer processes caused by near-surface chemical reactions and optical interactions is investigated.In the first chapter, the charge transfer between InGaN/GaN NWH electrodes and an aqueous electrolyte in presence of ascorbic acid, uric acid and hydrogen peroxide (H(2)O(2)) was investigated by simultaneous photoluminescence (PL) and photocurrent (PC) measurements.The analysis revealed that the acidic dissociation of these molecules modifies the surface charge in the NW resulting in a reduction of the barrier height and surface band bending (SBB), respectively. These electrodes allow for the detection of the molecules by oxidation due to a transfer of photo-generated holes. Furthermore, the detection of ascorbic acid with uric acid and H(2)O(2) as background signals as well as the identification of H(2)O(2) with ascorbic and uric acid as background signals is shown.In the second section of this chapter, the charge transfer processes between GaN NW electrodes and covalently immobilized charge separation triad molecules are analyzed. The excitation of the photoactive triad molecules resulted in a modulation of the PC. The increase of the anodic PC was attributed to a direct electron transfer via the photoactive fullerenes or by the decrease of the barrier height due to dipole formation at the interface.Simultaneous PL and PC measurements proved the establishment of a negative charge at the interface which increases the effective SBB and thus, enhances the charge transfer between photo-generated charge carriers from the NW and the electrolyte. Additionally, the experiments revealed that the presence of surface states is relevant for the performance of the electrode.In the second chapter of this work, InGaN/GaN NWH arrays as optochemical electrodes in combination with a standard optical microscope were used for the optical readout and imaging of biochemical processes that are based on local changes of the pH or the electrical potential. The resolution limits were studied and a bias resolution of delta U(C) less or equal 1 mV, a pH resolution of delta pH less or equal 0.03 and a time resolution of delta t less or equal 50 ms could be shown. The imaging of biochemical processes with chemical contrast was demonstrated by the investigation of the sodium/proton exchanger of isolated crypts of rats. It is shown that quantitative analysis of the pH changes with a spatial resolution of below delta x less than 0.63 micrometer is possible.Hence, it is demonstrated that the photoelectrochemical analysis of InGaN/GaN NWH and GaN NW electrodes allows the identification of the interfacial reactions as dynamic equilibrium by monitoring the PL and PC which serve as measurand for the SBB. In addition, the NWH arrays allow for bioimaging by providing high spatial and temporal resolution.
Gruppe III-Nitrid-Nanodrähte als multifunktionale optische Biosensoren
Keywords: ddc:530